DEVELOPMENT OF LONGITUDINAL STABILIZATION AND AUTOPILOT CONTROL SYSTEM FOR A FIXED WING AIRCRAFT - Sengtin, BO
The development of longitudinal stabilization and autopilot control systems for a fixed wing aircraft is discussed in this thesis. A flight dynamic model of a fixed wing aircraft is constructed and then used as the basis for control system design. The aircraft model, which later is integrated with the control system to form a closed loop system, then are simulated numerically in MATLAB and SIMULINK environment, for control design analysis purpose. The longitudinal stabilization system is designed using linear state feedback pole-placement approach, computed based on the linearized form of the aircraft dynamic models. The feedback gain matrices are computed for several flight conditions such that the closed loop system will have better stability characteristics on those operating points. For the outer loop, speed hold, flight path control, and altitude hold systems are developed for the aircraft, such that they can maintain the aircraft flight variables (speed, flight path angle, and altitude) during some flight phases. These outer loop tracking controllers are developed using PID scheme. From the simulation results, the designed controllers can do their tasks satisfactorily. The stabilization controllers improve the stability of the aircraft at several flight conditions, while the tracking controllers provide good control for maintaining and/or regulating aircraft speed, flight path angle, and altitude.